Computational Thinking Ability of Grade IV Elementary School Students on Energi and Its Changes Material - Agustina, Siti; Sopandi, Wahyu; Sujana, Atep (Papanda Publisher, 2025)
Despite the emphasis on higher-order thinking skills in 21st-century learning, computational thinking skills among elementary school students remain underdeveloped. Many students rely on memorization instead of understanding the logical, systematic process of solving problems, particularly in science. This is evident in their inability to break down complex problems into smaller parts, identify interrelationships between components, and develop structured, step-by-step solution strategies. This indicates a gap between future competency needs and classroom learning practices. This study aims to examine and describe the computational thinking abilities of fourth-grade students in relation to energy and its changes. The study will determine if there is a problem with students' computational thinking abilities in this context. This study employed a descriptive quantitative method with a sample of 80 students from several elementary schools. The instrument used was a written test based on computational thinking indicators, including decomposition, pattern recognition, abstraction, and algorithms. The results showed that students' computational thinking ability was poor because the value range was 62. Students can identify patterns and organize problem-solving steps systematically. However, they still have difficulty abstracting information and breaking down complex problems into simpler parts. These findings underscore the importance of integrating learning activities that stimulate computational thinking skills early on, particularly in elementary school science education, and of applying appropriate models to enhance students' computational thinking abilities.